Base population structure studies for Macrobrachium Rosenbergii using microsatellite markers / Thamayanthi Nada Raja - Nada Raja, Thamayanthi (2011)
Giant freshwater prawn farming is startlingly increasing in Malaysia, yet little is known about the patterns of genetic diversity of its domesticated and wild stocks. Making use of populations with different gene resources is a way to increase genetic diversity of Macrobrachium rosenbergii in Malaysia. Availability of microsatellite markers (‘western’ form) which are highly polymorphic enables the divergence study of this species to be conducted for genetic improvement. This project successfully identified potential base populations for a genetic improvement program. Mean observed heterozygosity across four populations was in the range of 0.55 to 0.62 while the mean expected heterozygosity ranged from 0.85 to 0.87. Mean number of alleles was found to be the highest in the Kg Acheh population at 15.40. The highest genetic distance was found between Kampung Acheh and Sg Perak populations with a value of 1.29 with an Pairwise FST value of 0.15. Population Teluk Kumbar and Sg Perak showed a high genetic identity with a value of 0.57 and a low Pairwise FST value of 0.09. The Kg Acheh and Sg Perak populations were the most divergent among the other populations and are the best pair to be crossed. For a successful genetic improvement program, genetic relatedness between parents from different locations is crucial. Many farm operators are mixing different populations for the sake of genetic diversity without having a proper genetics data. The number of different populations does not confirm the accumulation of variant alleles where genetic bottleneck could happen without proper relatedness data.